2009
DOI: 10.1007/s00432-009-0591-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models of hepatocellular carcinoma: developments and evolution

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies in the world. The biological mechanisms of hepatocarcinogenesis and progression are poorly understood. Experimental models of HCC provide valuable tools to evaluate the risk factors, new treatment modalities and biologic characteristics. Under the constant evolution in model design and technology development, new experimental models continue to emerge, including spontaneous models, induced models, viral models, transplantable models, and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 114 publications
(83 reference statements)
0
48
0
1
Order By: Relevance
“…The results usually are comparable to that found in humans [99]. Each model appears to have its own advantages and disadvantages [100]. Recent studies, including our own, demonstrated the usefulness of modeling human cancer in diethylnitrosamine (DEN)-induced in rats [54] as well as in genetically engineered mice [97,101].…”
Section: Animal Models and Comparative Genomics Of Hccmentioning
confidence: 68%
“…The results usually are comparable to that found in humans [99]. Each model appears to have its own advantages and disadvantages [100]. Recent studies, including our own, demonstrated the usefulness of modeling human cancer in diethylnitrosamine (DEN)-induced in rats [54] as well as in genetically engineered mice [97,101].…”
Section: Animal Models and Comparative Genomics Of Hccmentioning
confidence: 68%
“…Synopsis of the criteria for the "ideal" animal models to be taken under consideration when selecting and designing chemically induced models for HCC. [34][35][36][37][38]41 Advance HCC has no effective treatment or cure, despite the discovery of promising novel therapeutic drugs. The failure of treatments to improve the patients' survival should be related to tumor heterogeneity and to hepatic dysfunction.…”
Section: Animal Models and Hcc Researchmentioning
confidence: 99%
“…2,3,6 Chemically-induced models are time-consuming. 2 Intraportal or intrasplenic injection of tumor cells requires a surgical procedure and the possibility of peritoneal seeding. 4,5 Development of transgenic mouse models is time-consuming and expensive.…”
mentioning
confidence: 99%
“…4,5 Development of transgenic mouse models is time-consuming and expensive. 2,6,7 The ideal model of liver cancer should faithfully reproduce the key biological characteristics, be reliable, reproducible, affordable and easy to manipulate. 2,7,8 None of the currently available mouse models meets all the criteria of an ideal animal model, which include biological, genetic, etiological and therapeutic criteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation